Pulmonary hypertension alters blood flow distribution and impairs the hyperemic response in the rat diaphragm - Schulze, Kiana M.; Horn, Andrew G.; Weber, Ramona E.; Behnke, Bradley J.; Poole, David C.; Musch, Timothy I. (Frontiers in Physiology, 2023)
Pulmonary hypertension (PH) is characterized by pulmonary vascular remodeling, respiratory muscle and cardiac impairments, and exercise intolerance. Specifically, impaired gas exchange increases work of the diaphragm; however, compromised contractile function precludes the diaphragm from meeting the increased metabolic demand of chronic hyperventilation in PH. Given that muscle contractile function is in part, dependent upon adequate blood flow (Q ̇), diaphragmatic dysfunction may be predicated by an inability to match oxygen delivery with oxygen demand. We hypothesized that PH rats would demonstrate a decreased hyperemic response to contractions compared to healthy controls. Methods: Sprague-Dawley rats were randomized into healthy (HC, n=7) or PH (n=7) groups.PH rats were administered monocrotaline (MCT) while HC rats received vehicle. Disease progression was monitored via echocardiography. Regional and total diaphragm blood flow and vascular conductance at baseline and during 3 minutes of electrically-stimulated contractions were determined using fluorescent microspheres. Results: PH rats displayed morphometric and echocardiographic criteria for disease (i.e., acceleration time/ejection time, right ventricular hypertrophy). In all rats, total costal diaphragm Q ̇ increased during contractions and did not differ between groups. In HC rats, there was a greater increase in medial costal Q ̇ compared to PH rats (55 ± 3 vs. 44 ± 4%, P<0.05), who demonstrated a redistribution of Q ̇ to the ventral costal region. Conclusions: These findings support a redistribution of regional diaphragm perfusion and an impaired medial costal hyperemic response in PH, suggesting that PH alters diaphragm vascular function and oxygen delivery, providing a potential mechanism for PH-induced diaphragm contractile dysfunction.